2021
DOI: 10.3389/fphar.2021.637801
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol in Pharmacoresistant Epilepsy: Clinical Pharmacokinetic Data From an Expanded Access Program

Abstract: Background and Aim: Data on the clinical pharmacokinetics of cannabidiol (CBD) are scanty. We explored the effect of demographic and clinical variables on plasma concentrations of purified CBD in patients with Dravet (DS) and Lennox–Gastaut syndrome (LGS).Methods: The study design was an open, prospective, multicenter expanded access program (EAP). Venous blood samples were drawn from patients between 8 and 9 am, before the CBD morning dose, 12 h apart from the last evening dose, and then 2.5 h after their usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…During the follow-up period, 68.5% of the patients with at least 1 month of treatment remained on CBD, relatively in line with the other EAPs at 12 months (~60%) ( 11 ) and studies with no TREs (63–81%) ( 16 ). Bearing in mind the limitation of the low number of patients treated, we found that the retention rate for adults was significantly higher than that for pediatric patients; this parameter is not accompanied by a significant difference on seizures, but it is worth noting that in our ancillary study on CBD plasma concentrations, we observed that concentration/dose ratio is significantly lower in patients younger than 18 years ( 17 ). Also in this latter case, no correlation was found between dose, plasma concentration, and efficacy, and further studies are warranted to understand whether this low trough CBD concentration is meaningfully linked to efficacy and safety.…”
Section: Discussionmentioning
confidence: 64%
“…During the follow-up period, 68.5% of the patients with at least 1 month of treatment remained on CBD, relatively in line with the other EAPs at 12 months (~60%) ( 11 ) and studies with no TREs (63–81%) ( 16 ). Bearing in mind the limitation of the low number of patients treated, we found that the retention rate for adults was significantly higher than that for pediatric patients; this parameter is not accompanied by a significant difference on seizures, but it is worth noting that in our ancillary study on CBD plasma concentrations, we observed that concentration/dose ratio is significantly lower in patients younger than 18 years ( 17 ). Also in this latter case, no correlation was found between dose, plasma concentration, and efficacy, and further studies are warranted to understand whether this low trough CBD concentration is meaningfully linked to efficacy and safety.…”
Section: Discussionmentioning
confidence: 64%
“…Several trials have proved its effectiveness in DS and LGS patients ( Devinsky et al, 2017 ; Lattanzi et al, 2019 ; Verrotti and Striano 2021 ). A highly purified plant-based form of oral CBD formulation was approved by the Food and Drug Administration (FDA) in 2018 and the European Medicines Agency (EMA) in 2019 for the treatment of seizures associated with DS and LGS ( Contin et al, 2021 ). Cenobamate, a novel tetrazole-derived carbamate compound, has been recently approved in the United States for the treatment of partial-onset seizures in adult patients [Keam 2020] ( Löscher et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, these findings should be taken with caution due to the limited number of patients and the high intersubject variability in CB's plasma concentrations at a given dose, observed both with Sativex® and Bediol®. Many factors can contribute to this generally recognized variability, such as subject characteristics (i.e., age, body composition) ( 31 , 32 ), drug peculiar pharmacokinetics ( 15 , 24 ), pharmaceutical characteristics (i.e., poor CB's recovery in oils and variable stability over time) ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%